Neuroinflammation in a Rat Model of Tourette Syndrome - Zhongling, Ke; Yanhui, Chen; Guofeng, Chen; Yanyan, Liu (Frontiers in Behavioral Neuroscience, 2022)
Objective Tourette syndrome (TS) is a group of childhood-onset chronic neuropsychiatric disorders characterized by tics, i.e., repetitive, sudden, and involuntary movements or vocalizations, which is often associated with various psychopathological and/or behavioral comorbidities, including attention deficit hyperactivity disorder (ADHD), obsessive-compulsive disorder (OCD), anxiety, depression, and sleep disorders and have a worse prognosis. The mechanism of TS is still not clear. The relationship between immune activation, neuroinflammation, and neuropsychiatric disorders has attracted much attention in the past two decades. To explore the underlying mechanism in TS, the relationship between neuroinflammation and behavioral alterations in TS rats was investigated in this study. Methods A total of 36 Sprague-Dawley male rats were divided into three groups randomly as follows: the TS, control (CON), and drug intervention groups. The TS rat group was treated with haloperidol (Hal) (the TS + Hal group). The TS rat model was established using 3,3-iminodipropionitrile (IDPN), which is a well-known animal model of TS. The behavioral syndromes, brain tissue cytokines, like interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-α), and microglial activation of the three groups were assessed. Results The behavioral scores of rats in the TS group and the TS + Hal group were higher than those in the CON group (P < 0.05), but the scores of behavioral tests in the TS + Hal group were lower than those in the TS group (P < 0.05). The levels of IL-6 and TNF-α in the rat brain tissue were significantly higher in the TS group than in the CON group (P < 0.05), while no significant differences were found between the CON group and the TS + Hal group (P > 0.05). The microglia was significantly activated in the TS group and slightly activated in the TS + Hal group, which was considerably less than that in the TS group. Conclusion The IDPN-induced TS rats had significant neuroinflammation in the brain, and the interaction between dopamine (DA) dysregulation and immune dysfunction may play a vital role in the pathogenic mechanisms of TS.